2014
DOI: 10.1371/journal.pone.0093363
|View full text |Cite
|
Sign up to set email alerts
|

Contact Force and Scanning Velocity during Active Roughness Perception

Abstract: Haptic perception is bidirectionally related to exploratory movements, which means that exploration influences perception, but perception also influences exploration. We can optimize or change exploratory movements according to the perception and/or the task, consciously or unconsciously. This paper presents a psychophysical experiment on active roughness perception to investigate movement changes as the haptic task changes. Exerted normal force and scanning velocity are measured in different perceptual tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 25 publications
(39 reference statements)
4
42
0
Order By: Relevance
“…The finger slid in the medial radial direction, from right to left and left to right (figure 4), and one test consisted of four cycles of 40 mm. Owing to the linear motor operating limits, the finger scanning speed was lower than the more spontaneous velocities encountered during natural active tactile exploration which are close to 40 mm s 21 [46].…”
mentioning
confidence: 87%
“…The finger slid in the medial radial direction, from right to left and left to right (figure 4), and one test consisted of four cycles of 40 mm. Owing to the linear motor operating limits, the finger scanning speed was lower than the more spontaneous velocities encountered during natural active tactile exploration which are close to 40 mm s 21 [46].…”
mentioning
confidence: 87%
“…Tanaka et al (2014) demonstrated that humans use a greater variation in contact force for the smooth stimuli than for the rough stimuli. Introducing the adequate exploratory movement into the sensor on the basis of findings on human haptic bidirectionality and fingertip characteristic might enhance the evaluation capability of the sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding normal force, it might be difficult to maintain a large constant normal force, especially for an uneven surface. Here, Tanaka et al (2014) conducted roughness perceptual task using similar samples and normal force and scanning velocity exerted in the spontaneous exploratory movement can be observed to be around 0.5 N and around 100 mm/s. Similar values can be also observed in other related psychophysical experiments .…”
Section: Intensity Of Sensor Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers measured the interaction force between the fingertip and material surfaces as reliable information related to the finger pad's deformation because the forces cause the skin to deform [13][14][15][16][17][18][19]. For example, Wiertlewski et al [13] precisely measured the interaction forces when a material slid beneath a fingertip.…”
Section: Introductionmentioning
confidence: 99%